MENGHADIRI PERAYAAN HARI BESAR AGAMA NON ISLAM PERSPEKTIF AL-QUR’AN - Faldiansyah, Iqrom (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2019)
In the context of attending the commemoration of other religions' holidays in the view of the Qur'an, there are almost no verses that specifically discuss the issue of "attending the celebrations of other religions". Based on the search for various commentary books online and offline related to the issue of "attending other religious celebrations", there are indeed opinions that strictly prohibit (forbid) and there are also opinions that allow. Their opinions are based on several verses which they make as evidence (argument) in addressing the problem of attending to the commemoration of non-Islamic religious holidays. As for those who prohibit referring to the surah, among others; Al-Qur'an surah al-Furqon verse 72, Al-Qur'an surah al-Kafirun verses 1-6, Al-Qur'an surah al-An'am verse 108, Al-Qur'an surah al-Mumtahanah verse 8. Whereas those who are allowed to attend non-Islamic holidays will refer to the following verses; Al-Qur'an surah Al-An'am verse 108, Al-Qur'an surah al-Mumtahanah verse 8, Al-Qur'an surah al-Kafirun verses 1-5, Al-Qur'an surah Al-Furqon verse 72. The purpose of this paper is for consideration for Muslims to find out about the context of attending the celebrations of other religions (non-Islamic). Furthermore, the approach used in this paper is the Al-Qur'an approach which is explained through interpretation. Hopefully, this article is useful for readers and can be used as an illustration to find out the opinions of people who allow and expect to attend other (non-Islamic) Gama holidays.